The Actualization of Pancasila from the Legal Perspective within the Academic Environment of University. - Saputri, Ernia Duwi; Lestari, Sely Ayu (IKIP PGRI Bojonegoro, 2024)
The individuals within the university community, encompassed in the academic society, constitute a vital component of the nation that functions as supporters of Pancasila values. Indonesia as a nation that acknowledges God, emphasizes humanity, unity, democracy, and social justice, regards Pancasila as a valuable foundation. This research aims to elucidate how Pancasila should be actualized within the educational environment, particularly from a legal perspective, focusing on IKIP PGRI Bojonegoro. The research question is: